2014
DOI: 10.1126/science.1253895
|View full text |Cite
|
Sign up to set email alerts
|

Specific disruption of thalamic inputs to the auditory cortex in schizophrenia models

Abstract: Auditory hallucinations in schizophrenia are alleviated by antipsychotic agents that inhibit D2 dopamine receptors (Drd2s). The defective neural circuits and mechanisms of their sensitivity to antipsychotics are unknown. We identified a specific disruption of synaptic transmission at thalamocortical projections in the auditory cortex in murine models of schizophrenia-associated 22q11 deletion syndrome (22q11DS). This deficit is caused by an aberrant elevation of Drd2 in the thalamus, which renders 22q11DS thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 22 publications
6
117
1
Order By: Relevance
“…Specifically, acute treatment with uncompetitive NMDAR antagonists PCP and MK-801 have been reported to induce attention impairments in the 5-CSRTT (for review, Amitai and Markou, 2010). We and Young and colleagues have shown task dependent deficits in the 5C-CPT in male mice (Kelly et al, 2014) and female rats (Chun et al, 2014), we have also shown deficits induced by our subchronic PCP treatment regime (Eddins et al, 2014), however neither group has systematically investigated sex differences in this task. See Hayward et al (2012, under review), for a very recent review of separation by performance in the 5C-CPT discussing all studies in this area in both male and female rodents.…”
Section: Attentionmentioning
confidence: 55%
“…Specifically, acute treatment with uncompetitive NMDAR antagonists PCP and MK-801 have been reported to induce attention impairments in the 5-CSRTT (for review, Amitai and Markou, 2010). We and Young and colleagues have shown task dependent deficits in the 5C-CPT in male mice (Kelly et al, 2014) and female rats (Chun et al, 2014), we have also shown deficits induced by our subchronic PCP treatment regime (Eddins et al, 2014), however neither group has systematically investigated sex differences in this task. See Hayward et al (2012, under review), for a very recent review of separation by performance in the 5C-CPT discussing all studies in this area in both male and female rodents.…”
Section: Attentionmentioning
confidence: 55%
“…Coupled with emerging ideas regarding how other genes in the 22q11 region could lead to psychosis (Chun et al, 2014; Fenelon et al, 2011; Fenelon et al, 2013; Paterlini et al, 2005; Xu et al, 2013), they represent a step towards a comprehensive understanding of the neurobiological consequences of the deletion syndrome. Such an understanding may eventually translate into bonafide improvements in the clinical management of patients who suffer from these consequences.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to define the molecular and cellular basis of the cognitive and behavioral deficits associated with the 22q11.2 microdeletion have focused on the effects of single gene mutations within the 22q11.2 microdeletion region (Bender et al, 2005; Chun et al, 2014; Fenelon et al, 2013; Harper et al, 2012; Hiramoto et al, 2011; Hsu et al, 2007; Huotari et al, 2004; Mukai et al, 2004; Murphy et al, 1999; Paterlini et al, 2005; Xu et al, 2013). Recently, we demonstrated that mice haploinsufficient for one of these genes, Zdhhc8 +/− , recapitulate several key aspects of the full microdeletion, including deficits in spatial working memory and functional connectivity (Mukai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The thalamus relays sensory inputs to the neocortex and modulates cognitive processes including memory, attention and decision-making (Mitchell et al, 2014). Recently, several studies have supported a correlation between neurodevelopmental/psychiatric disorders and defects in the thalamocortical neural network (Parnaudeau et al, 2013;Chun et al, 2014;Wells et al, 2016). Thalamocortical axons also have been shown to influence the survival and identity of postmitotic cortical neurons via thalamus-derived molecules including VGF (Sato et al, 2012;Li et al, 2013;Gerstmann and Zimmer, 2015).…”
Section: Remaining Questions and Future Applicationsmentioning
confidence: 99%